Linnaeus's Plantae Surinamenses revisited - Rodrigues de Moraes, Pedro Luis [UNESP] (Magnolia Press, 2012)
In 1775, Jacob Alm defended the Linnaean dissertation Plantae Surinamenses under the precidency of Carolus Linnaeus. In this account of Surinamese plants preserved in alcohol, given to Linnaeus by the King Gustavus III of Sweden, 148 species were treated, 117 of them with species names determined. Fifteen other species were indicated as new, but were neither described nor named, and 16 species were identified only to genus level. Here, the taxonomic identity and nomenclatural status of those names are updated and discussed. Five of the 117 names and also 11 of their synonyms, a species name described by Rottboll and ten described by Linnaeus filius are lectotypified. Two new combinations and a new name are proposed, and two new synonyms are established.
Keywords: Carolus Linnaeus; Suriname; Carl Gustaf Dahlberg; Daniel Rolander; taxonomy; lectotypification; nomenclature